2004
DOI: 10.1097/00000542-200412000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Significance of Cardiac Troponin I Release in Severe Trauma Patients

Abstract: Serial electrocardiogram recordings and troponin I assessments may be proposed for initial screening in high-risk trauma patients to detect anatomical cardiac injuries through the time course of circulating protein. Troponin I release does not have a prognosis value in trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 0 publications
1
40
1
1
Order By: Relevance
“…On the other hand, Edouard et al [59] distinguished three groups of patients according to the time course of troponin I, three groups of patients were defined a priori: very transient (B12 h) and limited release (troponin I \ 2 lg/l), transient (B36 h) and significant release (troponin I C 2 lg/l), and sustained ([36 h) and significant release (troponin I [ 2 lg/l). Unfortunately, according to these authors, although a sustained and significant release of troponin I was frequently associated with chest trauma, a significant myocardial contusion may occur without troponin I release and, moreover, troponin I release does not have a prognostic value in trauma patients.…”
Section: Troponin I and Traumamentioning
confidence: 99%
“…On the other hand, Edouard et al [59] distinguished three groups of patients according to the time course of troponin I, three groups of patients were defined a priori: very transient (B12 h) and limited release (troponin I \ 2 lg/l), transient (B36 h) and significant release (troponin I C 2 lg/l), and sustained ([36 h) and significant release (troponin I [ 2 lg/l). Unfortunately, according to these authors, although a sustained and significant release of troponin I was frequently associated with chest trauma, a significant myocardial contusion may occur without troponin I release and, moreover, troponin I release does not have a prognostic value in trauma patients.…”
Section: Troponin I and Traumamentioning
confidence: 99%
“…Pregnancy was also a noninclusion criterion. The care of the patients was directed by the same existing protocols as previously described and was not modified by the study (20). Initially, volume loading was given to obtain a mean arterial pressure Ն70 mm Hg, a hemoglobin level Ն8 g/dL, a prothrombin time Յ16 secs, and a platelet count Ն75·10 9 platelets/L.…”
Section: Study Populationmentioning
confidence: 99%
“…However, several reports have thrown doubt on the usefulness of cTnI, BNP, and D-dimer. There have also been negative reports on the ability of cTnI for predicting the prognosis of trauma 17) and for detecting myocardial contusion 18,19) . Also, another report found that there was no relationship between the D-dimer level and the prognosis of ICU admitted patients 20) .…”
Section: Discussionmentioning
confidence: 99%